Bio-inspired synthesis of amino acids modified sulfated cellulose nanofibrils into multivalent viral inhibitors via the Mannich reaction. (1st January 2023) - Hu, Songnan; Li, Yuehu; Yue, Fengxia; Chen, Yian; Qi, Haisong
Abstract: Virus cross-infection via surfaces poses a serious threat to public health. Inspired by natural sulfated polysaccharides and antiviral peptides, we prepared multivalent virus blocking nanomaterials by introducing amino acids to sulfated cellulose nanofibrils (SCNFs) via the Mannich reaction. The antiviral activity of the resulting amino acid-modified sulfated nanocellulose was significantly improved. Specifically, 1 h treatment with arginine modified SCNFs at a concentration of 0.1 g/mL led to a complete inactivation of the phage-X174 (reduction by more than three orders of magnitude). Atomic force microscope showed that amino acid-modified sulfated nanofibrils can bind phage-X174 to form linear clusters, thus preventing the virus from infecting the host. When we coated wrapping paper and the inside of a face-mask with our amino acid-modified SCNFs, phage-X174 was completely deactivated on the coated surfaces, demonstrating the potential of our approach for use in the packaging and personal protective equipment industries. This work provides an environmentally friendly and cost-efficient approach to fabricating multivalent nanomaterials for antiviral applications. Graphical abstract: Unlabelled Image Highlights: Amino acids were successfully introduced to SCNFs by the Mannich reaction. Amino acid-modified SCNFs could greatly enhance the antiviral performance. Bio-inspired virus-blocking nanomaterials were fabricated without toxic solvent.